Comparative Analysis of Cellulosic Ethanol Production from Lignocellulosic Substrate Moringa oleifera Using Kluyveromyces marxianus and Zymomonas mobilis - Shanmugam Sivarathnakumar; Khalid A. Al-Ghanim; Marcello Nicoletti; Marimuthu Govindarajan; Baskar Gurunathan (Fermentation, 2023)
In the current investigation, the woody stem of Moringa oleifera was processed by chipping and milling and was subsequently exposed to a combination of pretreatments involving a 3% v/v solution of nitric acid and autohydrolysis. The simultaneous saccharification and fermentation (SSF) of the pretreated hydrolysate of M. oleifera was conducted using Zymomonas mobilis and Kluyveromyces marxianus in occurrence of commercial cellulase enzyme, Tween 80, and sodium azide. The fermentation process parameters for Z. mobilis were optimized individually, including a substrate concentration of 5% (w/v), concentration of inoculum 5% (v/v), pH 5.4, and temperature 34 °C. Similarly, for K. marxianus, the process parameters were optimized individually, with a substrate concentration of 5% (w/v), an inoculum concentration of 3% (v/v), a pH of 5.1, and a temperature of 41 °C. The highest cellulosic ethanol concentration was achieved by the micro-organism K. marxianus after a fermentation period of 96 h.